INCREASE THE ACCURACY OF DETERMINING THE VALUES OF HARMONIC COMPONENTS IN ELECTRICAL SIGNALS - G. P. Mussonov; A. S. Seleznev; V. V. Fedchishin (Известия высших учебных заведений: Проблемы энергетики, 2018)
In the work, the urgency of increasing the accuracy of determining the values of the harmonic components in electrical signals is substantiated. It is shown that it is necessary to take into account the nonlinear character of the change in the circuit inductance to increase the accuracy of determining the amplitude and / or effective values of the higher harmonic components in the primary circuit. Fast-acting algorithms for the accurate determination of the values of harmonic components are described. Results of full-scale tests using the proposed methods are presented. Comparison of the above algorithms for processing secondary signals is performed.